Otimização superestrutural de biorrefinaria de cana-de-açúcar com hidrólise e gaseificação da biomassa vegetal e biodigestão da vinhaça e do licor de pentoses - Fonseca, Gabriel de Castro (2018)
The production of ethanol in sugarcane biorefineries generates large amounts of by-products such as straw, bagasse and vinasse. The objective of this work was to develop and implement a tool for the analysis of investments within the framework of a sugarcane ethanol bio-refinery (E1G) designed to take advantage of all these by-products in the production of second generation ethanol (E2G) and electricity. The combustion of bagasse in low pressure boilers for energy self-sufficiency of the process is a widely used technology. Not all distilleries, however, adopt the technology to produce surplus electricity. Two alternatives for the production of these surpluses were examined: the combustion of straw and bagasse in high pressure boilers (Rankine cycle) and biomass integrated gasification combined cycle (BIGCC). The impact of biogas production by anaerobic digestion of vinasse on the techno-economical viability of the process was also investigated, since the production of second generation ethanol leads to vinasse throughputs even larger than those observed in traditional distilleries. An autonomous distillery with capacity to process 3.84 million tons of cane per harvest and recovery of 50 % of straw from the field was considered. The economic analysis was based on factored-cost estimates and on superstructural optimization in order to define the optimal fraction of hydrolyzed bagasse and the best process for energy production. The uncertainty regarding the economic analysis was estimated by the Monte Carlo method. Different case studies were evaluated assuming changes in product prices, reduction in investment costs due to technological learning effects and expectations for the long-term scenario. In most scenarios the optimal operation involved the generation of electricity by combustion of biomass in high pressure turbines and in all scenarios, the optimum involved the hydrolysis of all bagasse and the production of biogas. Nonetheless, under the conditions evaluated in this work, none of the scenarios evaluated were deemed economically feasible, suggesting that these technologies are not yet sufficiently mature for commercial use without support from the public sector.